Development of Discovery Learning Model Learning Tools to Improve Students' Physical Critical Thinking Ability - Maya Astika; Hikmawati Hikmawati; Sutrio Sutrio; Gunawan Gunawan (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2021)
This development research aims to produce a product in the form of a discovery learning model to improve students' critical thinking skills in physics. The research design used is the 4D model which consists of define, design, develop and disseminate. Products developed in the form of a syllabus, lesson plans (RPP), material analysis, student worksheets (LKPD), and test instruments in the form of description questions. Data collection techniques using validation sheets and questions. The validity data were analyzed by determining the final mean value (NA) of the expert validators and practitioners. The improvement of critical thinking skills is analyzed using standard gain from the results before and after the learning process. Data validity results show that the learning device developed is at a very valid level with a final average value of 3.48 so that the developed device is suitable for use in learning. The data on the reliability results of the learning tools developed with an average value of 93.21% were included in the reliable category. The ability to think critically with discovery learning models has increased with a gain value of 0.38. Based on the results of these data, it can be concluded that the discovery learning model that was developed is effective to improve students' critical thinking skills in physics.Keywords: Learning tools, discovery learning model, critical thinking skills in physics